Synthesis of ReI tricarbonyl complexes with various sulfur‐ and oxygen‐donating ligands: crystal structures of two ReI dinuclear structures bridged by S atoms. Issue 10 (13th September 2018) - Nkoe, Pheello I.; Visser, Hendrik G.; Swart, Chantel; Brink, Alice; Schutte-Smith, Marietjie
Abstract : The structures of two dinuclear Re I complexes are reported, one with a 2, 2′‐sulfanediyldi(ethanethiolate) bridging ligand and the other with three 2‐methoxybenzenethiolate bridging ligands. Two mononuclear Re I complexes have also been characterized by spectral methods. Abstract : The synthesis and characterization of two dinuclear complexes, namely fac ‐hexacarbonyl‐1κ 3 C, 2κ 3 C ‐(pyridine‐1κ N )[μ‐2, 2′‐sulfanediyldi(ethanethiolato)‐1κ 2 S 1, S 3 :2κ 3 S 1, S 2, S 3 ]dirhenium(I), [Re2 (C4 H8 S3 )(C5 H5 N)(CO)6 ], (1 ), and tetraethylammonium fac ‐tris(μ‐2‐methoxybenzenethiolato‐κ 2 S : S )bis[tricarbonylrhenium(I)], (C8 H20 N)[Re2 (C7 H7 OS)3 (CO)6 ], (2 ), together with two mononuclear complexes, namely (2, 2′‐bithiophene‐5‐carboxylic acid‐κ 2 S, S ′)bromidotricarbonylrhenium(I), (3 ), and bromidotricarbonyl(methyl benzo[ b ]thiophene‐2‐carboxylate‐κ 2 O, S )rhenium(I), (4 ), are reported. Crystals of (1 ) and (2 ) were characterized by X‐ray diffraction. The crystal structure of (1 ) revealed two Re—S—Re bridges. The thioether S atom only bonds to one of the Re I metal centres, while the geometry of the second Re I metal centre is completed by a pyridine ligand. The structure of (2 ) is characterized by three S‐atom bridges and an Re…Re nonbonding distance of 3.4879 (5) Å, which is shorter than the distance found for (1 ) [3.7996 (6)/3.7963 (6) Å], but still clearly a nonbonding distance. Complex (1 ) is stabilized by six intermolecular hydrogen‐bond interactions and an O…O interaction, while (2 ) is stabilized by two intermolecular hydrogen‐bond interactions and two O…π interactions.